2012
DOI: 10.1002/ett.2514
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability analysis of elliptic curve cryptography‐based RFID authentication protocols

Abstract: Radio Frequency Identification (RFID), we show that three recently proposed RFID authentication protocols which rely exclusively on the used of Elliptic Curve Cryptography are not secure against the tracking attack. To make this attack successfully, the adversary needs to execute three phases. Firstly, the attacker just eavesdrops on the messages exchanged between Server and Tag. Secondly, the attacker impersonates Server to reply with the same random number that is obtained from previous phase. Finally, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…We enumerate the functionalities comparison of the proposed protocol and some other related protocols in Table . Obviously, it can be observed that the proposed scheme can satisfy all the security requirements of the RFID system and is more secure (or with equivalent security performances) than the most recent related protocols . In contrast, according to the recent survey made by He and Zeadally, only 3 recently proposed ECC‐based authentication schemes suitable for the health‐care environment could satisfy all 7 selected security requirements (mutual authentication, confidentiality, anonymity, availability, forward security, scalability, and attack resistance) .…”
Section: Security Analysismentioning
confidence: 95%
“…We enumerate the functionalities comparison of the proposed protocol and some other related protocols in Table . Obviously, it can be observed that the proposed scheme can satisfy all the security requirements of the RFID system and is more secure (or with equivalent security performances) than the most recent related protocols . In contrast, according to the recent survey made by He and Zeadally, only 3 recently proposed ECC‐based authentication schemes suitable for the health‐care environment could satisfy all 7 selected security requirements (mutual authentication, confidentiality, anonymity, availability, forward security, scalability, and attack resistance) .…”
Section: Security Analysismentioning
confidence: 95%
“…For all authorised users, obviously there are m n C m unknown variables (i.e. all elements of A and E y) whereas there are only m n equations in Equation (5). Obviously, there are an infinite number of solutions of A and E y in Equation (5).…”
Section: Security Analysismentioning
confidence: 99%
“…all elements of A and E y) whereas there are only m n equations in Equation (5). Obviously, there are an infinite number of solutions of A and E y in Equation (5). That is, although all authorised users can collude to build the equations of Equation (5), they cannot obtain the right values of A and E y by solving Equation (5) because the number of unknown values is far more than that of known equations.…”
Section: Security Analysismentioning
confidence: 99%
“…There are three roles in a typical RFID system: tags that are embedded in objects to be identified, readers that emit radio signals to interrogate tags and a server that maintains all tags' information, identifies tags and provides services. On the basis of the resource limitation and the operations supported on tags, RFID protocol can be divided into four classes: (i) full-fledged, supporting encryption or public key algorithms [1][2][3][4][5][6], (ii) simple, supporting pseudo random number generator and hash functions [7][8][9][10][11][12][13][14][15][16][17][18], (iii) lightweight, supporting pseudo random number generator and checksum functions [19], and (iv) ultralightweight, supporting only bitwise operations [20][21][22]. In this paper, our approach makes tags compute nothing but only fetching memory, and the resource cost for such tags is estimated as the cost in simple class.…”
Section: Introductionmentioning
confidence: 99%